Análise da atuação da enfermagem em Centro Dia para pessoas idosas: um estudo multicaso - Barros, Maraiza Amato Pereira (2022)
Population aging happens at an accelerated rate in Brazil and in the world. Government measures have been taken to establish public policies that help improve the quality of life and ensure all rights for this population. Among them are the non-asylum modalities for independent or semi-dependent elderly people and, therefore, it is extremely important to understand the importance of a nursing professional inserted in the multiprofessional team and what are their challenges in the face of intersectoral actions. The objective of the present study is to analyze the importance of the role of nursing professionals in social assistance services in the region of the Regional Directorate of Development and Social Assistance of Ribeirão Preto for care for the elderly, exclusively in Day Centers for the Elderly, regarding interprofessionality and intersectoriality. This is a multi-case study in Day Centers for the Elderly chosen and belonging to the Regional Directorate of Development and Social Assistance of Ribeirão Preto-SP. The sample consisted of nursing professionals and managers of these social facilities. Data collection was carried out through a remote interview carried out by the Google Meet platform, previously scheduled by means of an email invitation to the participants and which took place after reading and agreeing to the Free and Informed Consent Form. The collected data were recorded and transcribed in full for content and narrative analysis. The results indicate that the performance of nursing professionals in Day centers for the Elderly presented important findings on the differentiated clinical view and humanized care of this professional, about the relevance of interprofessionality in ensuring quality and resolution care and pointed out considerable aspects about intersectoriality and the challenges faced. It is expected that this study can generate subsidies to contribute to the improvement of social assistance, intersectoral and health policies aimed at the elderly assisted in Day Centers for the Elderly, through the insertion of the qualified nursing professional as part of the multidisciplinary team.